Características nutricionais e fatores associados com sobrepeso e obesidade em adolescentes atendidos em ambulatório da Faculdade de Ciências Médicas de Minas Gerais em Belo Horizonte - Eduardo Vial Faria (2007)
Objective: Evaluation of nutricional state, overweight and obesity frequency and associations with possible risk factors; evaluation of the frequency of arterial hypertension, anemy and dyslipidemy in adolescents attended in ?